2015
DOI: 10.1038/nature15251
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function p53 mutants co-opt chromatin pathways to drive cancer growth

Abstract: SUMMARYTP53 is the most frequently mutated gene among all human cancers. Prevalent p53 missense mutations abrogate its tumor suppressive function and lead to “gain-of-function” (GOF) that promotes cancer. Here we show that p53 GOF mutants bind to and upregulate chromatin regulatory genes, including the methyltransferases KMT2A (MLL1) and KMT2D (MLL2), and acetyltransferase KAT6A (MOZ or MYST3), resulting in genome-wide increases of histone methylation and acetylation. Analysis of The Cancer Genome Atlas shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
397
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(439 citation statements)
references
References 42 publications
27
397
2
4
Order By: Relevance
“…47 Of relevance to K14.ROCK er /HK1.ras 1205 carcinogenesis, p21 overexpression protected NEMO Dhepa animals against DNA damage, 39,41 whereas p21 knockout accelerated hepato-carcinogenesis in bi-genic NEMO Dhepa /p21 null mice, 47 thus implicating NF-κβ in chromosomal damage. 33,39,41,45 Most major consequences of ROCK2 activation alter the tumour microenvironment and establish a context permissive for stage-specific progression. 1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Of relevance to K14.ROCK er /HK1.ras 1205 carcinogenesis, p21 overexpression protected NEMO Dhepa animals against DNA damage, 39,41 whereas p21 knockout accelerated hepato-carcinogenesis in bi-genic NEMO Dhepa /p21 null mice, 47 thus implicating NF-κβ in chromosomal damage. 33,39,41,45 Most major consequences of ROCK2 activation alter the tumour microenvironment and establish a context permissive for stage-specific progression. 1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…loss and the lack of DNA repair would give rise to additional mutations in highly proliferative cells giving a susceptibility to malignant conversion. 32,33 Indeed, as outlined below, these K14.ROCK er /HK1.ras 1205 data suggest a mechanism involving p53 loss which links ROCK2-associated NF-κβ deregulation to the matrix remodelling that drives progression [34][35][36][37] when coupled to GSK3β/β-catenin/WNT signalling effects. 5 20,23,41 All wdSCCs exhibited persistent basal-layer p21 expression, which exactly paralleled K14.ROCK er /pMypt1 expression suggesting that increased p21 is a common response to ras/ROCK er /ROCK2 activities.…”
Section: Rock2 Activation Co-operates With Ras Ha To Elicit Malignantmentioning
confidence: 93%
“…TP53 gain-of-function-mutant proteins have recently been shown to interact with ETS transcription factors and to up regulate genes controlling H3K4 methylation activity, such as MLL1. Thus, some missense TP53 mutants may fall into chromatin regulator or epigenetic categories [141].…”
Section: Deregulation Of Histone Methylation In Cllmentioning
confidence: 99%
“…Zhu et al noticed that mutant p53 cells are sensitized to COMPASS methyltransferase complex inhibitors in vitro, 6 while we found that mutant p53 induces resistance to proteasome inhibitors (such as carfilzomib), which can be overcome in TNBC xenografts by targeting of mutant p53 by APR-246 (PRIMA-1MET). 2 Now these approaches, that could provide simple therapeutic strategies to target a large number of tumors bearing different mutant p53 proteins, need to be progressed toward the clinical tests.…”
mentioning
confidence: 89%
“…6 Strikingly, in the common mutant p53 DNA-interactome Zhu and coworkers found other broad process effectors -methyltranferases (MLL1, MLL2) and an acetyltranferse (MOZ), whose Ets2-mediated activation by mutant p53 leads to epigenetic reprogramming and increased cancer growth. 6 Thus, epigenetic modification, proteome reshaping and miRNA modulation mechanisms joined the earlier-discovered mutant p53-dependent genomic instability 7 in the set of mechanisms that globally drive the molecular landscape of the cell toward transformation (Fig. 1).…”
mentioning
confidence: 99%